2022
DOI: 10.3390/diagnostics12071710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of BAP1-Tumor Predisposition Syndrome by a Multitesting Approach: A Ten-Year-Long Experience

Abstract: Germline mutations in the tumor suppressor gene BRCA1-associated protein-1 (BAP1) lead to BAP1 tumor predisposition syndrome (BAP1-TPDS), characterized by high susceptibility to several tumor types, chiefly melanoma, mesothelioma, renal cell carcinoma, and basal cell carcinoma. Here, we present the results of our ten-year experience in the molecular diagnosis of BAP1-TPDS, along with a clinical update and cascade genetic testing of previously reported BAP1-TPDS patients and their relatives. Specifically, we se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Many studies have focused on genetic mutations [ 5 , 30 ] or epigenetic mechanisms [ 31 ] of mesothelioma and found common patterns with other cancers. Several findings have suggested a potential role for BAP1 in the carcinogenesis of numerous malignancies [ 32 , 33 , 34 , 35 ]. BAP1 is an oncosuppressor protein that acts as a deubiquitinase and is involved in gene expression and chromatin regulation [ 34 , 35 , 36 ]; it is commonly inactivated in mesotheliomas [ 7 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on genetic mutations [ 5 , 30 ] or epigenetic mechanisms [ 31 ] of mesothelioma and found common patterns with other cancers. Several findings have suggested a potential role for BAP1 in the carcinogenesis of numerous malignancies [ 32 , 33 , 34 , 35 ]. BAP1 is an oncosuppressor protein that acts as a deubiquitinase and is involved in gene expression and chromatin regulation [ 34 , 35 , 36 ]; it is commonly inactivated in mesotheliomas [ 7 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several findings have suggested a potential role for BAP1 in the carcinogenesis of numerous malignancies [ 32 , 33 , 34 , 35 ]. BAP1 is an oncosuppressor protein that acts as a deubiquitinase and is involved in gene expression and chromatin regulation [ 34 , 35 , 36 ]; it is commonly inactivated in mesotheliomas [ 7 , 37 , 38 , 39 , 40 ]. Germline BAP1 mutations underpin the BAP1 tumor predisposition syndrome (BAP1-TPDS).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, germline variants associated with KURIS have been reported as somatic tumor variants in a handful of patients. 3,17 T A B L E 1 Reported germline variants of BAP1 associated with tumor predisposition syndrome 1 (TPDS1) or Kury-Isidor syndrome (KURIS). As mentioned earlier, these variants elevate the risk of multiple cancer types, characterized by aggressiveness, rapid growth, and earlier onset compared to sporadic cases.…”
Section: Bap1 Functionmentioning
confidence: 99%
“…This may be due to underreporting of family histories that are not cancer related. Nevertheless, germline variants associated with KURIS have been reported as somatic tumor variants in a handful of patients 3,17 …”
Section: Bap1 Functionmentioning
confidence: 99%
“…In general, carriers of the germline BAP1 pathogenic variant (PV) develop tumors at a younger age as compared to patients with the same sporadic tumors [6] (Table 3). A recent Italian study by Sculco et al [33] describing a ten years in the molecular diagnosis of BAP1-TPDS sequenced germline DNA samples from 101 individuals with suspected BAP1-TPDS and validated PVs by assessing BAP1 somatic loss in matching tumor specimens. Overall, the authors found seven patients (7/101, 6.9%) carrying six different germline BAP1 PVs, including one novel variant.…”
Section: Role Of Bap1 Protein Loss In the Diagnosis Of Bap1 Syndromementioning
confidence: 99%